FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENJADI GURU PADA MAHASISWA PAI FITK UNSIQ WONOSOBO - Naurah Nazhifah Trisnaeni; Maryono Maryono; Salis Irvan Fuadi (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
This study aims to determine the factors that influence the interest in becoming a teacher in PAI FITK UNSIQ Wonosobo students. Interest is a person's interest in something that becomes his desire. This study uses qualitative research methods with data collection techniques, namely observation, interviews, and documentation. Respondents in this study were the Chair of the PAI Study Program and students of PAI FITK UNSIQ Wonosobo. Data analysis techniques in this study used an interactive analysis model according to Miles & Huberman which included data collection, data reduction, data presentation, and conclusions or verification. The results of this study indicate that the factors that influence the interest in becoming a teacher are internal factors such as emotional factors, perceptions, motivation, talent, and mastery of knowledge. While external factors include the family environment and social environment. Students are interested in becoming PAI teachers because they have certain reasons that strengthen students to become teachers. For example, students have been interested in becoming teachers since they were young and have a talent that must be developed through activities related to the teaching profession.